Use of Acupuncture in the Rehabilitation Treatment of Patients with Parkinson's Disease - Julio López Argüelles; Omar Morejón Barroso (Revista Finlay, 2023)
Acupuncture is a very effective and safe technique for treating the symptoms of Parkinson's disease. The practice of this technique has among its benefits: reducing signs and symptoms, improving motor functions, reducing the need for medication, minimizing medication side effects, slowing the progression of the disease, increasing dopamine levels, decreasing neuronal damage and death, increase cyclophilin levels, increase the number of stem cells and the number of neurons transformed from them, and enhance antioxidant systems. For years it has been postulated that the insertion of needles causes the release of endorphins and that it promotes local blood flow.